2018
DOI: 10.2147/dddt.s166749
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide modified oleate adenosine prodrug lipid nanocarriers for the treatment of myocardial infarction: in vitro and in vivo evaluation

Abstract: PurposeMyocardial infarction is a major cause of mortality and heart failure worldwide. One of the most effective methods of this injury is direct delivery of cardioprotective drugs to ischemia–reperfusion (IR) myocardium. The aim of the present study was to fabricate an adenosine (Ade) prodrug-based, atrial natriuretic peptide (ANP)-modified nanosystem for the treatment of myocardial infarction.Materials and methodsOleate adenosine prodrug (Ade-OA) and ANP-distearoylphosphatidylethanolamine-polyethylene glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…ANP/PKG signaling pathway can regulate the K ATP channel of ventricular cardiomyocytes [40]. ANP modi ed adenosine oleate precursor drugs have a better therapeutic effect on acute myocardial ischemia in rats [41]. In this study, SGI signi cantly inhibited the expressions of ANP and BNP mRNA, and signi cantly reduced the expressions of SP1 and GATA4 mRNA at the upstream and Prkg1a mRNA at the downstream, suggesting that SGI can play a protective role on the heart by inhibiting ANP and BNP.…”
Section: Discussionmentioning
confidence: 99%
“…ANP/PKG signaling pathway can regulate the K ATP channel of ventricular cardiomyocytes [40]. ANP modi ed adenosine oleate precursor drugs have a better therapeutic effect on acute myocardial ischemia in rats [41]. In this study, SGI signi cantly inhibited the expressions of ANP and BNP mRNA, and signi cantly reduced the expressions of SP1 and GATA4 mRNA at the upstream and Prkg1a mRNA at the downstream, suggesting that SGI can play a protective role on the heart by inhibiting ANP and BNP.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al. ( 2018 ) suggested that nanoparticles could elongate the circulation time of drugs in serum and have great potential to accumulate in the myocardial infarct area. The higher heart distribution of ANP/TPP-BN-LPNs than non-modified LPNs is in accordance with the aim of the study: to deliver more nanocarriers to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…ANP contained ligand was synthesized by conjugating APN-NH 2 to DSPE-PEG by amide bond to achieve ANP-PEG-DSPE (Yu et al., 2018 ). Briefly, EDC·HCl (1.2 equivalents) and NHS (1.2 equivalents) were added to DSPE-PEG (1 equivalent), stirred for 2 h to activate the carboxyl groups (solution A).…”
Section: Methodsmentioning
confidence: 99%
“…NPs have longer circulated properties than free drugs and can be targeted into the infarcted myocardium in a receptordependent process [80].…”
Section: Prodrug Of Oleate Adenosinementioning
confidence: 99%
“…Further study is needed to comprehensively analyze the toxicity, especially chemotoxicity and inflammatory responses. In addition, future work should plan to introduce novel ways to reduce toxicity, represented in Table 3 [77][78][79][80][81][82][83][84][85] and Table 4 [86][87][88][89].…”
Section: Nanomaterials Toxicitymentioning
confidence: 99%